Establecer estratégias de comunicación digital para la interacción usuario cliente en la Universidad Estatal de Bolívar, cantón Guaranda – Ecuador, año 2019 - Inca Copa, Deyci Karolina (2020)
This research project arises from the interest to know if the Bolívar State University has good Digital Communication Strategies for client user interaction, the institution to date has a total of 6075 students from different faculties and their respective schools. The research process was initiated with the field diagnosis, surveys aimed at students of the university, observation sheet for teachers in the area of System - Communication, Social Communication, and two students of the institution, to know what are the more appropriate communication channels, so that students can maintain an intercommunication with the institution, if the information transmitted by the university is of their interests, the periodicity in which they are issued among others. Thus ending with the objective of positioning the brand of the State University of Bolivar throughout the city of Guaranda with strategies already proposed, followed by a 50% increase in the number of followers on the official Facebook page of the institution all this in a 12 month term